Kualitas Sumber Daya Nelayan Tradisional di Desa Tunggulsari Kabupaten Rembang - Andayani Listyawati (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2014)
Traditional fishermen are part of a society with low level of welfare. Generally, traditional fishermen exploit sea treasury with simple instruments, low capital and depending on season. The fishes they get are still oriented for daily consumtion (subsistence), rather than to sell or reinvest for a bigger fishery business. The research on traditional fishermen in Tanjungsari Village is meant to describe human resources enhancement to access education and skill on oceanic and fishery resources. The approach used in this research is qualitative descriptive, data gathering are implemented through interview and documentary analysys technique, and data analysed through qualitative-descriptive technique. The result shows that human resources of traditional fishermen relatively are low. The indication can be seen form their education and skill related to fishery, that have an impact on the ability to solve their poverty and enhance their welfare. To increase their lives level, it is recommended that traditional fishermen should be given access to educuation, especially their skill to manage sea and fishery resources based on social value and culture of traditional fishermen community.